Marmota broweri Hall and Gilmore 1934 - Robert S. Hoffmann; Charles G. Anderson (Smithsonian Institution Press, 1993)
Marmota broweri Hall and Gilmore, 1934. Canadian Field Nat., 48:57. TYPE LOCALITY: USA, "Point Lay, Arctic Coast of Alaska " Restricted by Rausch (1953:117) to head of Kukpowruk River, Alaska. DISTRIBUTION: Brooks Range of N Alaska (USA) from near coast of Chukchi Sea to Alaska-Yukon border; perhaps also N Yukon (Canada). COMMENTS: Regarded as a synonym of caligata (Hall, 1981) but Rausch and Rausch (1965, 1971) and Hoffmann et al. (1979) considered broweri a distinct species. Published as part of Robert S. Hoffmann & Charles G. Anderson, 1993, Order Rodentia - Family Sciuridae, pp. 419-465 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 431, DOI: 10.5281/zenodo.7353130